The coverage of grain crops production with storage capacities in Serbia - Novković Nebojša; Novaković Tihomir; Mutavdžić Beba; Vukelić Nataša; Janošević Miljojko (Journal on Processing and Energy in Agriculture, 2018)
The subject of this paper is the annual production of important grain crops in Serbia (corn, wheat and soybean), as well as the available grain storage capacities (silos, floor storages and baskets). The aim of this research is to determine the utilization rate of grain crop storage capacities in Serbia as a whole and in four Serbian regions separately according to the average and extreme (maximum) production of the crops examined. On the basis of the analysis conducted, it was noted that the storage capacity in Šumadija, Western Serbia, the Belgrade region and Vojvodina was underutilized, whereas the production in Southern and Eastern Serbia exceeded the available storage capacities. Moreover, considering the data referring to floor storages and silos, it can be concluded that in Southern and Eastern Serbia, the average production exceeded the total available storage capacities by 7.3 %, whereas the maximum annual production was 13.7 % higher than the storage capacities. .